2012
DOI: 10.21608/jpp.2012.84188
|View full text |Cite
|
Sign up to set email alerts
|

Response of Giza 90 Cotton Cultivar to Foliar Application of Some Drought Tolerance Inducers Under Water Stress and High Temperature Condations in Upper Egypt

Abstract: Two field experiments were carried out in El-Mattana Agric. Res. St., Agric. Res. Cent., Luxor Governorate, Egypt during 2010 and 2011 seasons to study the response of Giza 90 cotton cultivar to the application of some drought tolerance inducers to increase the tolerance of cotton plants to drought under high temperature condations in Upper Egypt. The experimental design was a split plot with four replications. Main plots included two irrigation intervals (15 and 21 days) and sub plot included the foliar appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 5 publications
3
7
0
Order By: Relevance
“…A deficiency of B can also affect fiber quality presumably because of the role of B in cell wall growth. Similar results were obtained by Faris and Rokkedh (2008) and Hamoda (2012) found that elongation of cotton fiber required the presence of B. On the other hand, a decrease in fiber length and micronaire was reported for plants not receiving adequate B.…”
Section: Chemical Contentssupporting
confidence: 88%
“…A deficiency of B can also affect fiber quality presumably because of the role of B in cell wall growth. Similar results were obtained by Faris and Rokkedh (2008) and Hamoda (2012) found that elongation of cotton fiber required the presence of B. On the other hand, a decrease in fiber length and micronaire was reported for plants not receiving adequate B.…”
Section: Chemical Contentssupporting
confidence: 88%
“…Temz et al (2009) found that different humic acid treatments (seed soaking, foliar spray, seed soaking + foliar spray) insignificantly affected seed cotton yield as compared with the untreated control application of humic acid. However, Hamoda (2012) found that lint % was insignificantly effected by the humex treatments. The tallest cotton plants were produced due to foliar spraying of humex 5 cm 3 /L three times, while the shortest plants were produced from untreated plants (control treatment) in both seasons of study.…”
Section: -Seed Index (Weight Of 100 Cotton Seeds In Grams)mentioning
confidence: 88%
“…More et al (2018) revealed the positive effects of spraying with B on growth, fruit retention, and yield components of cotton. Kassem et al (2009), Hamoda (2012), and Karademir & Karadmir (2020) illustrated that foliar application of B gives the highest values in leaves content of N, P, K, Mg, B, Fe, Mn, and Zn and significantly increases the seed cotton yield compared to control. Mixed Ca-B is essential for pollen grain germination and pollen tube elongation by helping in successful fertilization or pollination and banning the abortion of flowers.…”
Section: Introductionmentioning
confidence: 99%
“…Drought conditions cause oxidative stress in cells due to a higher leakage of electrons toward O 2 during photosynthetic processes and an increase in reactive oxygen species (ROS) production (Ali & Ullah, 2020). Hamoda (2012) pointed out that irrigation interval every 3 weeks cause a significant reduction in plant height, number of fruiting branches, number of open bolls/plant and seed cotton yield. Emara et al (2015) and Gomaa et al (2019) demonstrated that drought conditions during plant growth and fruit retention are due to a significant reduction in cotton yield and fiber quality properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation